Estudio sobre conexión en paralelo de generadores utilizando relés de sincronización - Sangoquiza Suntaxi, Byron Santiago (2015)
When performing the synchronization of generators with the purpose to enter parallel to a SEP is necessary to know the basic electrical parameters intervening in this process to facilitate the implementation of these maneuvers, besides knowing the best choices that have to make this process it done efficiently and safely. Currently exist electronic equipment that perform synchronization automatically of generators, this is the case of relays synchronization and protection that allow synchronization and in some cases protect the generator of electrical failure. Selected four relays existing in the Ecuadorian market and analyze its features and benefits when synchronizing generators.